Glycemic control and antidiabetic drugs in type 2 diabetes mellitus patients with renal complications - Huri HZ; Lim LP; Lim SK (Drug Design, Development and Therapy, 2015)
Hasniza Zaman Huri,1,2 Lay Peng Lim,1 Soo Kun Lim3 1Department of Pharmacy, Faculty of Medicine, University of Malaya, 2Clinical Investigation Centre, University Malaya Medical Centre, 3Renal Unit, Department of Medicine, Faculty of Medicine, University of Malaya, Kuala Lumpur, Malaysia Background: Good glycemic control can delay the progression of kidney diseases in type 2 diabetes mellitus (T2DM) patients with renal complications. To date, the association between antidiabetic agents and glycemic control in this specific patient population is not well established.Purpose: This study aimed to identify antidiabetic regimens as well as other factors that associated with glycemic control in T2DM patients with different stages of chronic kidney disease (CKD).Patients and methods: This retrospective, cross-sectional study involved 242 T2DM inpatients and outpatients with renal complications from January 2009 to March 2014 and was conducted in a tertiary teaching hospital in Malaysia. Glycated hemoglobin (A1C) was used as main parameter to assess patients’ glycemic status. Patients were classified to have good (A1C <7%) or poor glycemic control (A1C ≥7%) based on the recommendations of the American Diabetes Association.Results: Majority of the patients presented with CKD stage 4 (43.4%). Approximately 55.4% of patients were categorized to have poor glycemic control. Insulin (57.9%) was the most commonly prescribed antidiabetic medication, followed by sulfonylureas (43%). Of all antidiabetic regimens, sulfonylureas monotherapy (P<0.001), insulin therapy (P=0.005), and combination of biguanides with insulin (P=0.038) were found to be significantly associated with glycemic control. Other factors including duration of T2DM (P=0.004), comorbidities such as anemia (P=0.024) and retinopathy (P=0.033), concurrent medications such as erythropoietin therapy (P=0.047), a-blockers (P=0.033), and antigouts (P=0.003) were also correlated with A1C.Conclusion: Identification of factors that are associated with glycemic control is important to help in optimization of glucose control in T2DM patients with renal complication. Keywords: glycemic control, type 2 diabetes, antidiabetic regimens, renal complications